Effectiveness of Structured Teaching Program on Knowledge Regarding Prevention and First Aid Management of Foreign Body Aspiration in Mothers of Toddler in Selected Rural Community - Jadhav, Priyanka; Deshpande, Rupali; Shinde, Ekta; Desoza, Florence (Innovational: Journal of Nursing and Healthcare, 2024)
Objectives: The primary objective of the study was to assess pre-test knowledge regarding prevention and first aid management of FBA in mothers of toddlers in selected rural community whereas the secondary objective was to evaluate effectiveness of structured teaching program on knowledge regarding prevention and first aid management of FBA in mothers of toddlers in selected rural community and to find out association between pre-test and post-test knowledge with selected demographic variables. Materials and Methods: A quantitative, quasi-experimental – one-group pre-test, post-test research design was used where 100 mothers of toddler were selected as sample for study using convenience sampling technique. The data collected using structured knowledge questionnaires. Data were analyzed using paired t-test and Chi-square test in the study. Pre-test was conducted on the same day and after 7 days, post-test was conducted to assess the gained in knowledge using the same structured knowledge questionnaire to mothers of toddler to assess the post test. Results: Most of the 64% of mothers of toddler were 18–24 years of age, majority 83% of the mothers of toddler were having primary educational background, maximum 98% of mothers of toddler were housewife/farming, maximum 90% of mothers of toddler were belonging to Hindu religion, 61% of the mothers were having two toddler children, 58% of the mothers of toddler were having male toddler child, 79% were not having previous knowledge related to FBA in children, 68% of mothers of toddler were not knowing about FBA in children, and 63% of mothers of toddler were living in joint family. The mean score for the pre-test was 13.72 and for post-test was 18.87. Paired t-test was applied and calculated t-value for knowledge (19.85) was more than the table value (1.66) at 99 degree of freedom for 0.05 level of significance. Hence, it was statistically interpreted that the structure teaching program was effective in improving the knowledge regarding prevention and first aid management of FBA in mothers of toddler in selected rural community and there was a significant association of post-test knowledge with demographic variables, that is, previous knowledge related to FBA in children (6.3528) was higher than the table value at 5% level of significance. Conclusion: Structured teaching program acts as a guiding key for mothers of toddler to solve the problems associated FBA.